PENGARUH PERSEPSI SISTEM INFORMASI AKUNTANSI TERHADAP MINAT PENGGUNAAN QRIS (STUDI KASUS PADA SELURUH MAHASISWA KOTA BENGKULU TAHUN 2025) - Iwin Arnova; Jumadi, Jumadi; Lusiana , Lusiana (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2025)
This study aims to analyze the effect of accounting information system perception on students’ interest in using the Quick Response Code Indonesian Standard (QRIS) among students in Bengkulu City in 2025. The research employs a quantitative approach with an associative-correlational method. A total of 80 respondents were selected using the Slovin formula with a 5% margin of error. Data were collected through validated and reliable questionnaires and analyzed using multiple linear regression with t-test, F-test, and coefficient of determination (R²). The results show that accounting information system perception has a positive and significant effect on students’ interest in using QRIS. The determination coefficient (R²) of 0.916 indicates that 91.6% of the variation in QRIS usage interest is explained by the perception of accounting information systems. The better the perception of accuracy, relevance, and reliability, the higher the interest in using QRIS. This finding highlights the importance of accounting information literacy and digital financial education in promoting cashless payments among students. Keywords: Accounting Information System Perception, QRIS, Usage Interest, Students